Naringenin protects against acute pancreatitis-associated intestinal injury by inhibiting NLRP3 inflammasome activation via AhR signaling - Yan, Xu; Lin, Tianjiao; Zhu, Qingyun; Zhang, Yushi; Song, Zhimin; Pan, Xinting (Frontiers in Pharmacology, 2023)
Background: In this study, we examined the functions and mechanisms by which naringenin protects against SAP (severe acute pancreatitis)-related intestinal injury by modulating the AhR/NLRP3 signaling pathway. Material and methods: Fifteen healthy male C57BL/6 mice were randomly divided into SAP (n = 12) and normal (n = 3) groups. Mice in the SAP group received caerulein and lipopolysaccharide intraperitoneal injections and were then randomly assigned to the SAP, NAR, CH223191, and Dexamethasone (DEX) groups. Pathological changes in the pancreatic and intestinal mucosa were observed by Hematoxylin & Eosin (H&E) staining. In vitro, RAW264.7 cells were exposed to lipopolysaccharide and treated with naringenin. The levels of NLRP3, AhR, IL-1β, TNF, and IL-6 in the SAP model and RAW264.7 cells were evaluated by enzyme-linked immunosorbent assay (ELISA), quantitative real-time PCR (qRT-PCR), western blot, and immunohistochemistry. The nuclear translocation of AhR was shown by immunofluorescence. AutoDockTools was used to predict the conformations of naringenin-AhR binding, and PyMol 2.4 was used to visualize the conformations. Results: Mouse pancreatic and intestinal injury was alleviated by treatment with naringenin. Naringenin inhibited the activation of the NLRP3 inflammasome and inhibited damage to intestinal tight junctions. Moreover, naringenin increased AhR nuclear translocation and activated the AhR pathway. Conclusion: Naringenin can reduce SAP-associated intestinal injury by inhibiting the activation of the NLRP3 inflammasome via the AhR signaling pathway.